Reduction and shaping of graphene-oxide by laser-printing for controlled bone tissue regeneration and bacterial killing. (13th December 2017) - Palmieri, Valentina; Barba, Marta; Di Pietro, Lorena; Gentilini, Silvia; Braidotti, Maria Chiara; Ciancico, Carlotta; Bugli, Francesca; Ciasca, Gabriele; Larciprete, Rosanna; Lattanzi, Wanda; Sanguinetti, Maurizio; De Spirito, Marco; et al.
Abstract: Graphene and graphene oxide (GO) are capable of inducing stem cells differentiation into bone tissue with variable efficacy depending on reductive state of the material. Thus, modulation of osteogenic process and of bone mineral density distribution is theoretically possible by controlling the GO oxidative state. In this study, we laser-printed GO surfaces in order to obtain both a local photo-thermal GO reduction and the formation of nano-wrinkles along precise geometric pattern. Initially, after cells adhered on the surface, stem cells migrated and accumulated on the reduced and wrinkled surface. When the local density of the stem cells on the reduced stripes was high, cells started to proliferate and occupy the oxidized/flat area. The designed surfaces morphology guided stem cell orientation and the reduction accelerated differentiation. Furthermore the reduced sharp nano-wrinkles were able to enhance the GO antibacterial activity against methicillin-resistant Staphylococcus aureus (MRSA), a common cause of prosthetic joints infections. This strategy can offer a revolution in present and future trends of scaffolds design for regenerative medicine.